The Impact of Quality of Destination Attributes on Tourist Satisfaction #x2013; The Case of Bhutan (Global Journal of Management and Business Research, 2020)
Tourism is one of the world#x2019;s largest industries. In Bhutan, tourism is the second largest source of foreign exchange after hydroelectricity and the numbers of visitors are increasing. When destinations around the world are getting increasingly competitive calling for improved tourism destination attributes to attract international inbound tourists. This study sought to find out relationship between attributes and overall visitor satisfaction. The main questions that seek to find answers are whether the six attributes play role in determining the visitor satisfaction; to determine the influencing nature of socio-demographic features of international visitors to their satisfaction; and to determine if there exist relationship between tourist#x2019;s expectation and satisfaction. The analysis was carried out using secondary data collected by tourism council of Bhutan in 2016.A total of 34 variables with 6 attributes were chosen to test hypotheses. The findings show that all the attributes have significant relationship with overall satisfaction while the sociodemographic characteristics do not differ to affect the satisfaction.
Keywords: destination attributes; overall satisfaction; expectations; multiple regressions; bhutan